Analýza a návrh personálního informačního systému pro IT pracoviště ČVUT - Švehla, Albert; Albert Švehla (České vysoké učení technické v Praze, 2024)
Tato diplomová práce se zabývá analýzou a návrhem personálního informačního systému pro IT pracoviště na ČVUT. Cílem bylo identifikovat klíčové oblasti pro zlepšení a navrhnout řešení, která by podpořila střednědobou strategii pracoviště. Práce zahrnuje detailní analýzu současného stavu, definici strategických priorit, podrobný návrh řešení a porovnání jednotlivých variant implementace do současného prostředí. Jejich proveditelnost dále zkoumá implementovaný prototyp, na jehož základě jsou uvedena doporučení pro budoucí rozvoj personálního informačního systému.

This master's thesis focuses on the analysis and design of a human resource information system for the IT department at the Czech Technical University (CTU). The aim was to identify key areas for improvement and propose solutions that would align with the department's medium-term strategy. The work encompasses a detailed analysis of the current state, the definition of strategic priorities, a comprehensive solution design, and a comparison of various implementation approaches within the existing environment. The feasibility of these solutions is further explored through an implemented prototype, which serves as the basis for recommendations regarding the future development of the human resource information system.
Analysis and design of a human resource information system for the IT department of CTU
Keywords: personální informační systém; analýza; návrh; podniková strategie; prototyp; proof of concept; human resource information system; HRIS; analysis; design; business strategy; proof of concept